Neuroinﬂammation and COVID-19 ischemic stroke recovery—Evolving evidence for the mediating roles of the ACE2/angiotensin-(1–7)/mas receptor axis and NLRP3 inﬂammasome - Che Mohd Nasril, Che Mohd Nassir; Mohd Khairul Izamil, Zolkefley; Muhammad Danial, Ramli; Haziq Hazman, Norman; Hafizah, Abdul Hamid; Muzaimi, Mustapha (MDPI, 2022)
Cerebrovascular events, notably acute ischemic strokes (AIS), have been reported in the setting of novel coronavirus disease (COVID-19) infection. Commonly regarded as cryptogenic, to date, the etiology is thought to be multifactorial and remains obscure; it is linked either to a direct viral invasion or to an indirect virus-induced prothrombotic state, with or without the presence of conventional cerebrovascular risk factors. In addition, patients are at a greater risk of developing long-term negative sequelae, i.e., long-COVID-related neurological problems, when compared to non-COVID-19 stroke patients. Central to the underlying neurobiology of stroke recovery in the context of COVID-19 infection is reduced angiotensin-converting enzyme 2 (ACE2) expression, which is known to lead to thrombo-inflammation and ACE2/angiotensin-(1–7)/mitochondrial assembly receptor (MasR) (ACE2/Ang-(1-7)/MasR) axis inhibition. Moreover, after AIS, the activated nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) family pyrin domain-containing 3 (NLRP3) inflammasome may heighten the production of numerous proinflammatory cytokines, mediating neuro-glial cell dysfunction, ultimately leading to nerve-cell death. Therefore, potential neuroprotective therapies targeting the molecular mechanisms of the aforementioned mediators may help to inform rehabilitation strategies to improve brain reorganization (i.e., neuro-gliogenesis and synaptogenesis) and secondary prevention among AIS patients with or without COVID-19. Therefore, this narrative review aims to evaluate the mediating role of the ACE2/Ang-(1-7)/MasR axis and NLRP3 inflammasome in COVID-19-mediated AIS, as well as the prospects of these neuroinflammation mediators for brain repair and in secondary prevention strategies against AIS in stroke rehabilitation.